pH-sensitive charge-conversion cinnamaldehyde polymeric prodrug micelles for effective targeted chemotherapy of osteosarcoma in vitro - Deng, Jiapeng; Liu, Su; Li, Guoqing; Zheng, Yien; Zhang, Weifei; Lin, Jianjing; Yu, Fei; Weng, Jian; Liu, Peng; Zeng, Hui (Frontiers in Chemistry, 2023)
Chemotherapy is a common strategy for the treatment of osteosarcoma. However, its therapeutic efficacy is not ideal due to the low targeting, low bioavailability, and high toxicity of chemotherapy drugs. To overcome these side effects, we developed a pH-sensitive charge-conversion polymeric micelle (mPEG-b-P(C7-co-CA)) for osteosarcoma-targeted delivery of cinnamaldehyde (CA). First, an amphiphilic cinnamaldehyde polymeric prodrug (mPEG-b-P (C7-co-CA)) was synthesized through Reversible Addition-Fragmentation Chain Transfer Polymerization (RAFT) polymerization and post-modification, and self-assembled into spheric micelles with a diameter of 227 nm. Due to the protonation of the 2-(Hexamethyleneimino)ethanol (C7) group, mPEG-b-P(C7-co-CA) micelles can achieve charge conversion from a neutral to positive charge with decreasing pH. This charge-conversion property allows mPEG-b-P(C7-co-CA) micelles to achieve 143B cell targeting at pH 6.5. Finally, cellular uptake and MTT assay demonstrate that this pH-sensitive charge-conversion property can enhance the interaction of mPEG-b-P(C7-co-CA) micelles with osteosarcoma cells, enabling targeted delivery of CA, enhancing CA induced intracellular ROS levels and apoptosis of osteosarcoma cells. Therefore, mPEG-b-P(C7-co-CA) micelles can achieve osteosarcoma targeting effectively and enhance the anti-osteosarcoma effect of CA in vitro. This research provides a promising drug delivery system for clinical application and tumor treatment.